The role of intergenerational family stories in mental health and wellbeing - Elias, Alexa; Brown, Adam D. (Frontiers in Psychology, 2022)
Patterns of memory sharing begin early in one’s life, informing relationships, one’s history, and one’s sense of cultural belonging. Memory sharing among families has been the focus of research investigating the relationship between mental health and intergenerational memory. A burgeoning body of research is showing that intergenerational knowledge of one’s family history is associated with positive mental health and wellbeing. However, research on the specific mechanisms and potential applications of such findings are just beginning to emerge. In particular, studies examining intergenerational storytelling point to the importance of culture and gender as critical factors underlying how stories are told and the extent to which these stories are associated with wellbeing. Such findings hold important promise for the pentation and treatment of mental health issues. As research in this area continues to evolve, the identification and characterization of factors and mechanisms underlying intergenerational family stories and wellbeing may help to guide the integration of family stories into mental health interventions.